Conceptual Model of MIS for Integration of Halal and Green Practices in Clothing SMEs Based on SSM - Rahayu, Gina; Nisa Noviani Sudarman; Dicky Adjie (Candela Edutech Indonesia, 2025)
Small and Medium Enterprises (SMEs) in the apparel sector in Indonesia are increasingly pressured to comply with both halal standards and green sustainability practices. However, most SMEs lack a management information system capable of integrating these two aspects in a unified manner. This leads to limited process transparency, difficulties in regulatory compliance, and low competitiveness. Therefore, a systemic approach is required to design a solution that aligns with the complexity of the SMEs context. This study aims to develop a conceptual model of a management information system that integrates halal and green pactices in apparel SMEs using the Soft System Methodology (SSM). SSM is employed as the main approach to understand the problem situation, identify stakeholder perspectives, formulate the root definition and CATWOE, and construct a conceptual activity model. The management information systems (MIS) is designed to support planning, control, production process tracking, halal sertification documentation, and environmental performance monitoring. The study produces a conceptual model of an integrated management information system consisting of halal compliance, green performance, production, and managerial reporting modules. The model illustrates information flows, stakeholder interactions, and data requirements to support decision-making aligned with halal and green principles. The developed conceptual model provides a foundation for designing an adaptive and implementable management information system for apparel SMEs. The integration of halal and green principles through SSM enables a holistic, participatory, and context-specific system design. This research contributes to strengthening sustainable production systems and enhancing the competitiveness of apparel SMEs.